2013
DOI: 10.1021/nl304420b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Electrical Properties of Graphene Grown by Chemical Vapor Deposition via Controlling the Effects of Polymer Residue

Abstract: Residual polymer (here, poly(methyl methacrylate), PMMA) left on graphene from transfer from metals or device fabrication processes affects its electrical and thermal properties. We have found that the amount of polymer residue left after the transfer of chemical vapor deposited (CVD) graphene varies depending on the initial concentration of the polymer solution, and this residue influences the electrical performance of graphene field-effect transistors fabricated on SiO2/Si. A PMMA solution with lower concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
344
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 338 publications
(359 citation statements)
references
References 46 publications
14
344
1
Order By: Relevance
“…Their results indicated that the outstanding transport properties of graphene were indeed accessible on soft substrates, though large-area synthesized sheets are required for practical applications. Since then, synthesized graphene TFTs and circuits have made remarkable progress, featuring state-of-the-art TFT mobilities of B8,000 cm 2 V À 1 s À 1 , enabled by advancements in: (i) large-area chemical vapour deposited synthesis 52 , (ii) post-synthesis transfer 53 and (iii) transistor device structure 32,38,54 . Readers interested in graphene synthesis will find the 2010 review article by Chhowalla and coworkers 55 an excellent resource.…”
Section: Contemporary Flexible Performancementioning
confidence: 99%
“…Their results indicated that the outstanding transport properties of graphene were indeed accessible on soft substrates, though large-area synthesized sheets are required for practical applications. Since then, synthesized graphene TFTs and circuits have made remarkable progress, featuring state-of-the-art TFT mobilities of B8,000 cm 2 V À 1 s À 1 , enabled by advancements in: (i) large-area chemical vapour deposited synthesis 52 , (ii) post-synthesis transfer 53 and (iii) transistor device structure 32,38,54 . Readers interested in graphene synthesis will find the 2010 review article by Chhowalla and coworkers 55 an excellent resource.…”
Section: Contemporary Flexible Performancementioning
confidence: 99%
“…103 Polymer residues after fabrication processes affect the electrical and thermal properties of graphene. Plasma treatment can also be used as post process cleaning step for CVD grown graphene.…”
Section: Nitrogen Functionalizationmentioning
confidence: 99%
“…[13][14][15] The residue can alter the contact resistance as well as the electrical characteristics of the channel material. 14,16 Furthermore, the adhesion of a metal contact on the inert surface of a carbon nanotube is generally poor. 17 The contact can therefore delaminate during lift-off, and this undesired effect can significantly lower the device yield.…”
mentioning
confidence: 99%